Effect of Rhizobium Inoculation and Phosphate Fertilizer on The Growth of Soybean (Glycine max L) Grobogan Variety - Muhamad Nasir; Endang Tadjudin; Dwi Purnomo; Amran Jaenudin; Maryuliyanna (JURNAL SAINS NATURAL, 2023)
Various strategic efforts to increase food production continue to be made in an effort to achieve self-sufficiency and food security. Soybean is a national strategic commodity to support government programs in an effort to increase production with the aim of achieving self-sufficiency. The purpose of this study was to determine the effect of the combination of phosphate fertilizer and rhizobium biofertilizer on the growth of soybean (Glycine max L) Grobogan variety. The research was conducted from June to September 2022 at the Ma'had Al Zaytun Agricultural Complex, Indramayu Regency. The method used is the method of randomized block design with a combination pattern. There were 9 treatment combinations of SP-36 phosphate fertilizer and rhizobium inoculation. SP-36 Fertilizer consists of 3 levels, namely 100, 150 and 200 kg/ha and Rhizobium with 3 levels, namely 0.05, 0.10 and 0.15 g/planting hole. Each combination was repeated three times so that there were 27 trial plots. Each experimental plot is 6 m2. The observed data were processed using analysis of variance and the Scott-Knott test. The results showed.that the combination-of SP-36 Phosphate fertilizer-and Rhizobium inoculation had-a significant effect on all observations both plant height, number of trifoliate leaves, number of branches, root volume.